Indonesia's Participation in Responding to Global Warming Issues - Lisa Anisa; Raja Muhammad Firmansyah; Dadan M. Hamdani; Betha El Sherra; Rico Irvanda; Rahmad Wahyudi Putra; Dimas Tidar Febrian; Ryanda Lutfi Zaim; Yefrisyam Yefrisyam; Ebil Fuji Edison; Yandriansyah Yandriansyah; Skunda Diliarosta; Nurhasan Syah; Abdul Razak; Eri Barlian (Science and Environmental Journal for Postgraduate, 2021)
Global warming is characterized by an increase in the temperature of the atmosphere, sea, and land on earth. The occurrence of global warming will cause a series of extreme phenomena in nature in the form of changes in weather and climate that can pose a threat to the survival of life. Indonesia is an archipelagic country that has a high level of climate vulnerability, so it is highly affected by climate change. In addition to having great potential to be negatively impacted by climate change, Indonesia also has great potential to take part in mitigating and adapting to the negative impacts of climate change. This study aims to see how much effort has been made by Indonesia to participate in responding to the issue of global warming. This study uses the DPSIR (Driving force, Pressure, State, Impact, and Response) analysis method. With this analysis, it will be studied what triggers the issue of global warming, the pressures faced, the current environmental conditions or status, the perceived impact, and how the efforts have been made by the Government of Indonesia to address these issues.